Perbedaan Hasil Belajar Peserta Didik Kelas VII MTsN 1 Sidoarjo Sebelum dan Sesudah Penerapan Media Pembelajaran ICT - Khoirunnabila, Azza Ilma Khoirunnabila; Oksanda, Rizka Amalia; Indayati, Tatik; Kuswanto, Kuswanto (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2024)
Learning media is one of the most important factors in determining the success of the learning process. This study aims to determine the difference in learning outcomes of seventh grade students of MTs Negeri 1 Sidoarjo before and after implementing ICT learning media. The type of approach in this research is a quantitative approach with an experimental type using data collection techniques through pre-test and post-test. This study uses a One-Group Pretest-Posttest Design which is implemented only on one randomly selected group and no stability test is also done to clarify the condition of the group before being given treatment. The results of the research were analyzed using non-parametric tests, namely the Wilcoxon test, which produced a significance value of 0.001, which is smaller than 0.05. This shows that there is an increase between the pretest and posttest scores, which means there is a difference in student learning outcomes before and after using learning media.